A multi-modal systems extension to soft systems methodology - Mirijamdotter, Anita (Luleå, 1998)
This thesis develops a design method for social systems that do not fit the conventional industrial pattern and that consequently are not apt for regulation through mechanical means. It builds upon Soft Systems Methodology (SSM), one of the most widely used and well regarded of design methodologies. Yet, the systems science literature has identified some weaknesses in this methodology, and these have been confirmed in the critical evaluation and the empirical study of this thesis. It was found that SSM tends to be relativistic in normative issues, that its modelling is at times reductionistic and that there are philosophical inconsistencies between its different phases of design. THe task in this thesis has been to preserve the methodological strengths of SSM while at the same time attempt to correct its weakness by combining it with another systems sience approach: Multi-modal Systems Thinking. This approach incorporates a multi-dimensional framework of life and a management model to attain viability in social systems. The combination of SSM with this new framework results in a Multi-modal Soft Systems Methodology (Arvidsjaur Method for short) that has been tested empirically in a project for unemployed youth in Arvidsjaur, a small municipality in the north of Sweden. The Arvidsjaur Method is an effective tool in four ways. Firstly, it incorporates normative standards that overcome the criticisms regarding SSM's relativistic stance. Secondly, it enhances philosophical consistency in the complete design process. Thirdly, it provides a managerial design structure and fourthly, it offers a potential for designing systems that support a holistic, complete and dignified human life. Such an approach is also likely to assist us in appreciating different perspectives of our post- modern society and in making appropriate choices. Godkänd; 1998; 20060928 (evan)